Team Sports Off the Field: Competing Excludes Cooperating for Individual but Not for Team Athletes - Landkammer, Florian; Winter, Kevin; Thiel, Ansgar; Sassenberg, Kai (Frontiers in Psychology, 2019)
Both team and individual sports require competition, whereas cooperation is more prevalent in team than in individual sports. In particular, team athletes have to compete (for starting roles) while cooperating (for team success) with the same teammates. Therefore, the incompatibility between competition and cooperative behavior, a well-established phenomenon in psychological research, might pertain less for team athletes. In Study 1, team athletes attributed a higher demand to compete and cooperate with same others to their sport than individual athletes to their sport. Study 2 showed that experiencing competition (vs. control) undermines information sharing less for team than for individual athletes. In addition, Study 2 demonstrated that competition priming undermines the accessibility of cooperative thoughts less for team than for individual athletes. Therefore, team athletes and presumably members of work teams with similar experiences might be better at competing without ceasing to cooperate. Implications for collaboration in groups are discussed.